2009
DOI: 10.1051/0004-6361/200811498
|View full text |Cite
|
Sign up to set email alerts
|

Alpha effect and turbulent diffusion from convection

Abstract: Aims. We study turbulent transport coefficients that describe the evolution of large-scale magnetic fields in turbulent convection. Methods. We use the test field method, together with three-dimensional numerical simulations of turbulent convection with shear and rotation, to compute turbulent transport coefficients describing the evolution of large-scale magnetic fields in mean-field theory in the kinematic regime. We employ one-dimensional mean-field models with the derived turbulent transport coefficients t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
97
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 56 publications
28
97
2
4
Order By: Relevance
“…For unstratified convection with an imposed field Cattaneo & Hughes (2006) find that α diminishes for large magnetic Reynolds numbers, even for kinematically weak magnetic fields. With stratification, on the other hand, Käpylä et al (2008b) find val-ues of α that are compatible with those from simple estimates. They used the test-field method while Cattaneo & Hughes (2006) used an imposed field and estimate α as the ratio between the resulting field-aligned electromotive force and the imposed field.…”
Section: Implications and Open Problemssupporting
confidence: 67%
See 1 more Smart Citation
“…For unstratified convection with an imposed field Cattaneo & Hughes (2006) find that α diminishes for large magnetic Reynolds numbers, even for kinematically weak magnetic fields. With stratification, on the other hand, Käpylä et al (2008b) find val-ues of α that are compatible with those from simple estimates. They used the test-field method while Cattaneo & Hughes (2006) used an imposed field and estimate α as the ratio between the resulting field-aligned electromotive force and the imposed field.…”
Section: Implications and Open Problemssupporting
confidence: 67%
“…Another example is the case of rigidly rotating convection. Using the test-field method, Käpylä et al (2008b) noticed that with increasing rotation rate α increases and η t decreases. This led to the prediction that there should be α 2 dynamo action (i.e.…”
Section: Quenching For Equipartition-strength Fieldsmentioning
confidence: 99%
“…This value is above the critical Rm for dynamo excitation. Previous studies have shown that the turbulent transport coefficients for convection are independent of the magnetic Reynolds number provided that Rm is sufficiently larger than unity (Käpylä et al 2009a). Thus the results of this run can be considered representative of the present setup.…”
Section: Turbulent Transport Coefficientssupporting
confidence: 62%
“…Normalized profiles of the kinetic helicity, and the turbulent transport coefficients α xx , α yy , η t , η , γ and γ (from top to bottom) computed with the test-field method. also been found from convection with horizontal shear (Käpylä et al 2009a). In the case with vertical shear presented here, the relevant coefficient for this effect is not captured by the current version of the test-field method with only z-dependent test fields.…”
Section: Turbulent Transport Coefficientsmentioning
confidence: 82%
“…Often the coefficients are approximated by simple analytical functions of position, and their tensorial character is disregarded. Recently, the test-field method, developed by Schrinner et al (2005Schrinner et al ( , 2007) (see also Ossendrijver et al 2001Ossendrijver et al , 2002, allows one to determine all tensorial components of α and β directly from self-consistent numerical simulations (Brandenburg et al 2008;Käpylä et al 2009). These coefficients are sometimes strongly varying functions of position.…”
Section: Introductionmentioning
confidence: 99%